On-surface chemistry: directing and controlling chemical interactions - Judd, Chris (2020)
On-surface synthesis, where molecular building blocks react together to produce covalently bonded products, offers the potential for the generation of structures via alternative routes to those performed within traditional solution-phase chemistry. However, a better understanding of the mechanistic process of on-surface reactions, obtained through surface analysis techniques such as scanning probe microscopy, is first required in order to develop these reactions.